2014
DOI: 10.1074/jbc.m113.512079
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase of Regenerating Liver 2 (PRL2) Deficiency Impairs Kit Signaling and Spermatogenesis

Abstract: Background:The PRLs are oncogenic when overexpressed but their physiological function is not well defined. Results: PRL2-deficient mice exhibit testis hypotrophy, decreased sperm production, and impaired reproductive potential. Conclusion: PRL2 promotes Kit signaling and germ cell survival by down-regulating PTEN. Significance: The study reveals the biological importance of PRL2 in spermatogenesis and identifies PRL2 as a novel target for cancer and male contraception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
37
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 64 publications
8
37
1
Order By: Relevance
“…212 PRL2 and PRL3 were subsequently discovered by their sequence similarity to PRL1. Unlike many other PTPs that antagonize the action of protein kinases, the PRLs rank among the most oncogenic PTPs and function to promote activation of both ERK1/2 213217 and Akt 218221 , two of the key pathways that are abnormally up-regulated in cancer. PRLs are overexpressed in many cancer cell lines, and those with high level PRL expressions show increased proliferation, migration and anchorage-independent cell growth.…”
Section: Ptp Regulatory Mechanismsmentioning
confidence: 99%
“…212 PRL2 and PRL3 were subsequently discovered by their sequence similarity to PRL1. Unlike many other PTPs that antagonize the action of protein kinases, the PRLs rank among the most oncogenic PTPs and function to promote activation of both ERK1/2 213217 and Akt 218221 , two of the key pathways that are abnormally up-regulated in cancer. PRLs are overexpressed in many cancer cell lines, and those with high level PRL expressions show increased proliferation, migration and anchorage-independent cell growth.…”
Section: Ptp Regulatory Mechanismsmentioning
confidence: 99%
“…More recent in situ hybridization studies show ubiquitous PRL-2 mRNA expression across nearly all human tissues, suggesting that PRL-2 plays a role in fundamental physiological functions (Dumaual et al 2006). PRL-2 deficiency is associated with several altered phenotypes including increased serum Mg 2+ levels, decreased lymphocyte and neutrophil counts, and hypertrophy of the testicular germinal epithelium and placenta (Hardy et al 2014;Kobayashi et al 2014;Dong et al 2012Dong et al , 2014. PRL-2 knockouts also display elevated PTEN levels and decreased Akt phosphorylation (Dong et al 2012Stephens et al 2008).…”
Section: Introductionmentioning
confidence: 96%
“…Among the 3 PRLs, PRL2 is the most ubiquitously expressed in mammals (15,17). Moreover, analysis of PRL2-deficient mice revealed that PRL2 is required for proper placental development (18), spermatogenesis (19), and hematopoietic stem cell self-renewal (20).…”
Section: +mentioning
confidence: 99%